2019
DOI: 10.3390/ijms20061334
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB2 Promoter Hypomethylation as Recurrence Predictive Marker in Well-Differentiated Thyroid Carcinomas

Abstract: Despite the low mortality rates, well-differentiated thyroid carcinomas (WDTC) frequently relapse. BRAF and TERT mutations have been extensively related to prognosis in thyroid cancer. In this study, the methylation levels of selected CpGs (5-cytosine-phosphate-guanine-3) comprising a classifier, previously reported by our group, were assessed in combination with BRAF and TERT mutations. We evaluated 121 WDTC, three poorly-differentiated/anaplastic thyroid carcinomas (PDTC/ATC), 22 benign thyroid lesions (BTL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Point mutations in BRAF (codon 600), KRAS (codon 12/13), HRAS (codon 61), and KRAS (codon 61) were evaluated by pyrosequencing and RET rearrangements (RET/PTC1 and RET/PTC3) by RT-qPCR, as previously described (27). TERT promoter mutations (C228T and C250T hotspots) were investigated by direct Sanger sequencing, as described elsewhere (28).…”
Section: Detection Of Genomic Alterationsmentioning
confidence: 99%
“…Point mutations in BRAF (codon 600), KRAS (codon 12/13), HRAS (codon 61), and KRAS (codon 61) were evaluated by pyrosequencing and RET rearrangements (RET/PTC1 and RET/PTC3) by RT-qPCR, as previously described (27). TERT promoter mutations (C228T and C250T hotspots) were investigated by direct Sanger sequencing, as described elsewhere (28).…”
Section: Detection Of Genomic Alterationsmentioning
confidence: 99%
“…The effect of methylation alterations in thyroid carcinogenesis is demonstrated by downregulation of several tumor suppressors thyroid cancer cells, such as; TSHR, PTEN, RASSF1A, CDKN2A, DAPK1, TIMP3, ECAD, and RAP1GAP [193][194][195][196][197][198]. On the other hand, MAP17, CXCL12, HORMAD2, and PFKFB2 are hypomethylated and upregulated in aggressive thyroid cancer [199][200][201][202].…”
Section: Epigenetic Changes In Thyroid Cancermentioning
confidence: 99%
“…Genome-wide studies performed in different tumor types revealed methylome signatures able to stratify cancer subtypes [24], predict cancer outcomes [25][26][27][28], and identify epigenetic events related to inherent and acquired chemotherapy resistance [29]. Differential DNA methylation of specific CpG sites has contributed to the understanding of radiotherapy response with or without chemotherapy in a variety of cancer types, including glioblastoma, breast, gastric and colorectal cancers [30].…”
Section: Introductionmentioning
confidence: 99%